Anti-Cancer Constituents from Plants: Mini Review: Anti-Cancer Constituents from Plants: Mini Review - Islam, Mohammad Kaisarul; Barman, Animesh Chandra; Qais, Nazmul (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Now-a-days, cancer is a major concern globally, for which a large number of deaths occur annually, instead of the accessibility to various treatment options. Nevertheless, the latest treatment options are principally conglomerate with many side effects. Consequently, the development of an effective and competent anticancer therapy with the lower or minimum adverse or unwanted minor effect is the prime direction of research in the fields of natural product chemistry, drug design, and drug discovery. Phytochemicals available in plants have already been proven as prospective candidates in this regard. In general, phytochemicals are non-selective in their functions and restricted due to their differential activity on cancer cells along with the normal cells. As a consequence, researchers show their interest in isolating bioactive phytochemicals from nature with potent anticancer properties and generate lead compounds based on the natural skeleton of a molecule as a synthetic approach. Several phytomolecules have already been in existence for their in-vitro and in-vivo anticancer activities. This article deals with these lead phytomolecules from fifty-two species belong to thirty-five families with their reported mechanisms of action on nuclear and cellular factors involved in the treatment of carcinogenesis. Dhaka Univ. J. Pharm. Sci. 19(1): 83-96, 2020 (June)